Function approximation technique based sliding mode controller adaptive control of robotic arm with time-varying uncertainties - Mst., Nafisa Tamanna Shantaa; Zainul Azlan, Norsinnira (Elsevier B.V., 2015)
The controlling of robotic arm is really challenging due to the involvement of various uncertainties such as- time varying payload, friction and disturbances. These challenges attract many researchers to develop advanced control strategies for robot arm. However, most of the developed controllers focus on time invariant uncertainties. This paper presents the formulation of a new Sliding Mode Control- Function Approximation Technique (SMC-FAT) based adaptive controller for a robot arm carrying unknown time-varying payload with the presence of time-varying disturbance and friction. The limitation of previous controllers to cope up with wide range time-varying uncertainty is solved using FAT expression. The stability of the controller can be proven by selecting a proper Lyapunov function and the update law can be derived easily. Three different time-varying uncertainties in sinusoidal, sawtooth and random functions have been considered as the payload and disturbance in the computer simulation to evaluate the controller’s performance. The results with error less than 0.02 percentages proved the effectiveness of the proposed controller.